Mortimer - Munsch, Robert N., 1945-; Martchenko, Michael (Toronto : Annick Press, 1985)
Everyone tries to get Mortimer to be quiet at bedtime--his father, his mother, his seventeen brothers and sisters, and two policemen.
2.8
K-3
Keywords: Bedtime -- Fiction; Bedtime -- Fiction